L’impact de la crise financière de 2008-2009 sur les grandes universités américaines - Carole Masseys-Bertonèche (IdeAs)
This article focuses on the impact of the 2008-2009 financial crisis on the management of American universities. First, it analyses the changes that the American higher education system underwent in the last twenty years to adapt to previous economic crises. Then, it shows how the evolution of the sources of funding has made the universities more vulnerable in dealing with the 2008-2009 crisis. As a conclusion, it underlines the resilient factors of Top Research Universities and their adaptability to change in time of crisis.